A RANDOMIZED INVESTIGATION INTO THE USE OF ISOBARIC LEVOBUPIVACAINE AND ROPIVACAINE FOR SPINAL ANAESTHESIA DURING ELECTIVE LOWER LIMB ORTHOPAEDIC PROCEDURES, DHANBAD, INDIA. - Kumar, Mrituanjay; Sengar, Piyush Kumar (Student's Journal of Health Research Africa, 2024)
Background: Objectives: The investigation aimed to contrast the anesthetic activity of isobaric ropivacaine and levobupivacaine in lower limb orthopedic surgeries, examining their respective onset, duration of loss of motor and sensory functioning, as well as overall safety profile. Methods: A randomized, double-blind investigation spanning over a year was conducted at Shahid Nirmal Mahato Medical College in Dhanbad, Jharkhand, India to contrast the effectiveness of ropivacaine and levobupivacaine in orthopedic surgeries of lower extremities among 120 ASA Class I and II adult patients. Employing a shuffled sealed envelope method, participants were categorized into two cohorts (Group R and Group L), and various parameters, such as sensory blockade, motor blockade, and changes in the hemodynamic profile, in addition to safety, were assessed. Results: The investigation, involving 120 patients, categorized into Group R (Ropivacaine) and Group L (Levobupivacaine) revealed no statistically significant variations in the average time taken for surgery (81.23 min vs. 73.48 min). A similar observation was noted with the average time of commencement of sensory analgesic effect after 10 minutes (6.89 min vs. 9.24 min). The analysis of the loss of sensory and motor functioning, particularly in context with the average duration needed for the maximum level of blocking sensory functioning (12.45 min vs. 16.39 min) was comparable in both cohorts. Furthermore, both groups exhibited stable hemodynamics, and neither reported common complications. Conclusion: The study demonstrates comparable efficacy and safety profiles between isobaric ropivacaine and levobupivacaine in lower limb orthopedic surgeries, highlighting their interchangeability for anesthesia management in such procedures. Recommendation: The study recommends further research exploring specific patient populations or surgical contexts to refine anesthetic choices for enhanced clinical outcomes.